Comparative Efficacy of Tirzepatide Versus Semaglutide for Weight Loss in Adults With Overweight or Obesity: A Systematic Review and Meta‐Analysis of Head‐to‐Head Studies - Giovanna Pagani Paccola; Roberta Fernandes de Oliveira; Matheus Menão Mochetti; Fernanda Pataro Marsola Razera; Rafael Vecchi; Renan Canale Peres Montanher (Clinical Obesity, 2026)
ABSTRACT This systematic review and meta‐analysis aimed to compare the efficacy and safety of tirzepatide versus semaglutide for weight reduction in adults with overweight or obesity. We included randomised controlled trials and observational studies comparing tirzepatide and semaglutide with ≥ 24 weeks of follow‐up. The primary outcome was percentage weight change from baseline. Secondary outcomes included absolute weight change, weight‐loss thresholds, HbA1c and safety outcomes. Ten studies including 41 381 participants were analysed. Tirzepatide was associated with greater percentage weight reduction than semaglutide (MD −4.28 percentage points; 95% CI −5.28 to −3.28; p < 0.00001) and greater absolute weight loss (MD −4.43 kg; 95% CI −5.56 to −3.30; p < 0.00001). Tirzepatide was also associated with a higher likelihood of achieving ≥ 10%, ≥ 15% and ≥ 20% weight loss, with no difference at ≥ 5%. HbA1c reduction was greater with tirzepatide (MD −0.29%; p = 0.0002). Subgroup analyses by study design and type 2 diabetes status yielded consistent findings. There was no significant difference in treatment discontinuation due to adverse events (RR 1.28; p = 0.54), whereas serious adverse events were more frequent with tirzepatide (RR 1.83; p = 0.007). Overall and gastrointestinal adverse events were similar between groups. Tirzepatide was associated with greater weight reduction, greater glycaemic benefit and a higher likelihood of achieving weight‐loss thresholds than semaglutide, but with a higher risk of serious adverse events.